POLA MAKAN DAN INDEKS KENYANG PADA CAPLAK BETINA Rhipicephalus sanguineus (ACARI, IXODIDAE) - ., Leliana (Universitas Almuslim, 2014)
This aims of the research is to know feeding pattern, and engorgement index in female Rhipicephalus sanguineus. Feeding experiment were designed using the following female-male ratio 1:1. At same time every day up to detachment the body length, width and depth of females were measured using a caliper to the determine of body volume.Â The result of this research indicates that rate of engorgement indices in females (1:1 ratio) increased with increasing duration of attachment (P< 0.05) and the relationship between duration of tick attachment was above 90%. A significant increase in body cuticle extensibility occurs following copulation.Â Keywords: RhipicephalusÂ sanguineus, engorgement index, duration of attachment.